A Systematic Literature Review: the Effect of Tacit Knowledge Sharing on Employee Innovation - Aisyah Yudhawan, Shavira; Herachwati, Nuri (Journal La Sociale, 2025)
The rapid advancements in the industrial revolution 4.0 have reshaped business paradigms, prompting organizations to undergo transformative changes to maintain competitiveness. One critical factor for sustaining competitive advantage is innovation, which is closely tied to the effective utilization of knowledge resources, particularly tacit knowledge. Tacit knowledge, derived from individual experiences, is considered a vital asset due to its unique and non-replicable characteristics. This study aims to investigate the role of tacit knowledge sharing in enhancing employee innovation across various industrial sectors. Using a systematic literature review (SLR) methodology, this research synthesizes findings from numerous studies published between 2019 and 2024 to explore the relationship between tacit knowledge sharing and employee innovation. The review addresses three primary questions: the development of research in this field, implementation strategies in specific industries, and factors influencing the effectiveness of tacit knowledge sharing. Results reveal that tacit knowledge sharing significantly boosts employee innovation through improved creativity and problem-solving capabilities. However, its effectiveness depends on factors such as organizational culture, employee motivation, and interaction opportunities. Practical recommendations are provided to optimize knowledge-sharing processes, ultimately supporting organizational innovation and competitiveness in an era of rapid technological change.